Barriers and facilitators to accessing cancer care for people with significant mental health difficulties: A qualitative review and narrative synthesis. Issue 12 (8th November 2021) - Leahy, Dorothy; Donnelly, Alanna; Irwin, Kelly; D'Alton, Paul
Abstract: Objectives: Inequities in cancer care contribute to higher rates of cancer mortality for individuals with significant mental health difficulties (SMHD) compared to the general population. The aim of the current systematic review was to identify, appraise and synthesise qualitative evidence of patient and clinician/system barriers and facilitators to cancer screening and treatment for individuals with SMHD. Methods: We conducted a systematic search across three electronic databases in May 2020 and we carried out a second search across five electronic databases in January 2021. A narrative synthesis was conducted across eligible studies. Results: We identified the same six studies from both searches, with 133 individuals with SMHD and experiences of cancer care and 102 healthcare professionals. Key barriers to cancer care were related to patients' uncontrolled psychiatric symptoms and the adverse impact of their symptoms on engaging with cancer care; clinician barrier‐attitudes included stigmatising attitudes from clinicians and other staff towards individuals with SMHD and systems barrier‐fragmentation included the fragmentation of mental health and cancer care delivery. Key patient facilitators to accessing cancer care and completing cancer treatment included being connected with mental health services and controlled psychiatric symptoms. Stronger collaboration among healthcare professionals working across different sectors in addition to the development of a patient navigator role were identified as key facilitators to enhance patient care. Conclusions: Innovative approaches are needed to decrease mental health stigma, foster collaboration across disciplines, and facilitate the integration of timely mental health and cancer care for individuals with SMHD to address the mortality gap.